The Sources of Islamic Law on the Muamalah Concept About Contract Viewed on Philosophical Studies - Retnowati, May Shinta; Faruqi, Musta’an Al; Ihsan, Syahrul (University of Darusssalam Gontor, 2023)
••• English ••• Islamic law of the contract is used as the basis for muamalah transaction, which is oriented towards developing a general theory of Islamic law. This research is significant because of the birth of sharia institutions based on the provisions of Islamic contract and muamalah, as well as the growing business of Muslims accompanied by the emergence of a desire to harmonize business as a modern phenomenon, with the sharia principle. The methodology of this reseacrh, including normative Islamic law research, is to obtain concrete legal regulations which are the development of norms between Islamic legal doctrines, which are also derived from basic values in Al-Qur'an and Sunnah. The result is, based on the Islamic contract in Indonesia, several are used as basis in carrying out and forming the Islamic contract law. The purpose of implementing muamalah in philosophy is a contract that upholds socio-economic justice and income/welfare justice which are considered important components of Islamic moral philosophy. Islamic economic philosophy in this regard can be summarized in three aspects namely at-tauhid, al-’adalah, and maslahah, where the source of law is Al-Qur'an and Sunnah. ••• Indonesian ••• Hukum Islam dalam akad digunakan sebagai dasar transaksi muamalah, yang berorientasi pada pengembangan teori umum hukum Islam. Penelitian ini penting karena lahirnya lembaga syariah berdasarkan ketentuan kontrak Islam dan muamalah, serta berkembangnya bisnis umat Islam disertai dengan munculnya keinginan untuk menyelaraskan bisnis sebagai fenomena modern, dengan prinsip syariah. Metodologi dalam penelitian ini termasuk pada penelitian hukum Islam normatif, yakni untuk mendapatkan peraturan hukum yang konkret yang merupakan pengembangan norma-norma antara doktrin hukum Islam, yang juga diturunkan dari nilai-nilai dasar dalam Al-Qur'an dan Sunnah. Hasil yang didapat, berdasarkan akad Islam di Indonesia, beberapa digunakan sebagai dasar dalam menjalankan dan membentuk hukum kontrak Islam. Tujuan pelaksanaan muamalah pada filsafat adalah kontrak yang menjunjung tinggi keadilan sosial ekonomi dan keadilan pendapatan/kesejahteraan yang dianggap sebagai komponen penting dari filsafat moral Islam. Filsafat ekonomi Islam dalam hal ini dapat diringkas dalam tiga aspek yaitu at-tauhid, al-‘adalah, dan maslahah di mana sumber hukumnya adalah Al-Qur'an dan Sunnah.